Pertobatan Sejati Menghasilkan Transformasi Moral Dalam Kehidupan Daud: Studi Refleksi Mazmur 51 - Nggebu, Sostenis (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2024)
Abstract: The problem of this article is that repentance brought about a moral transformation in the life of King David. The text of Psalm 51 describes that King David fell into sin, but then he realized himself, repented and was sanctified by God. The method used to language this article is the study of passages.  The results show that Psalm 51 shows a deep spiritual need for God's people of all ages. Those who have fallen into self-conscious sin confess with all their hearts to God for the forgiveness that brings about moral renewal in their lives. The forgiveness experienced by David has been expressed in the form of a poem about the relationship of the prayer paradigm for forgiveness, whose meaning is actual. After receiving God's forgiveness, David regained a harmonious relationship with God, which brought about a moral renewal in his life. The same situation applies to the life of believers. Everyone who confesses his sins will be forgiven to experience the peace of Jesus Christ. Living in holiness is the moral standard required of every follower of Jesus Christ. Abstrak: Problem dari artikel ini tentang pertobatan yang mendatangkan transformasi moral dalam kehidupan Raja Daud. Dalam teks Mazmur 51, digambarkan bahwa Raja Daud yang jatuh dalam dosa, tetapi kemudian ia sadar diri, bertobat dari dosanya sehingga dikuduskan Allah. Metode yang digunakan untuk membahasa artikel ini adalah studi perikop. Hasilnya, menunjukkan bahwa Mazmur 51 memperlihatkan kebutuhan rohani yang mendalam bagi umat Allah dari segala zaman. Orang-orang yang telah jatuh dalam dosa sadar diri untuk mengaku dengan segenap hati kepada Allah demi pengampuan yang mendatangkan pembaruan moral di dalam kehidupan mereka. Pengampunan yang dialami Daud telah diungkapkan dalam bentuk puisi tentang hubungan paradigma doa untuk pengampunan, yang maknanya bersifat aktual. Daud dapat meraih kembali hubungan yang harmonis dengan Allah setelah memperoleh pengampunan Allah yang mendatangkan pembaruan moral dalam hidupnya. Situasi yang sama berlaku juga dalam kehidupan orang percaya. Setiap orang yang mengaku dosanya akan diampuni untuk mengalami damai sejahtera dari Yesus Kristus. Hidup dalam kekudusan menjadi standar moral yang dituntut dari tiap pengikut Yesus Kristus.